THE BENEFITS OF MULTIMEDIA LEARNING ON THE QUALITY OF UNDERSTANDING OF ELEMENTARY SCHOOL STUDENTS - Wafi Harahap; Lailatun Nur Kamalia Siregar; Nindya Putri; Azmi Oktari Harahap; Buti Sarma Sitompul; Khairina Habib Rangkuti; Tasya Sabrin (Journal of Quality Islamic Education Research, 2025)
This article aims to provide an alternative in integrating the benefits of multimedia learning. Learning is essentially used to develop a student's potential. Tools that can help the teaching and learning process are usually called learning media. In this discussion, we will discuss one of the learning media, namely multimedia. Multimedia is a media that describes two or more elements, for example media consisting of text, graphics, images, photos, audio, and animation. The benefits of using multimedia learning are to make the learning process more interesting, interactive, reduce the amount of learning time, improve the quality of student learning, the learning process can foster student interest and motivation to learn. The design of writing or compiling this article uses qualitative research or approach, this is because the results of our group discussions are obtained from literacy sourced from reading books about multimedia learning.